Perceptions of oral health among older Cambodians and their caregivers: A qualitative study. (11th December 2017) - Horn, Rithvitou; Heng, Chanlay; Chea, Chamrouen; Sieng, Chanthyda; Louv, Chenlay; Turton, Bathsheba; Durward, Callum; Abu Kasim, Noor Hayaty
Abstract : Objective: Older adults (those above the age of 60) are an emerging demographic in Cambodia, and very little is understood about their oral health experiences, needs, perceptions and behaviours. The aim of this study was to explore the oral health experiences, practices and perceptions of a convenience sample of a small but diverse group of older adults in Cambodia. Method: A cross‐sectional qualitative study in which focus group interviews were conducted by 5 trained senior Cambodian dental students. A convenience sample of 56 older adults and caregivers was recruited across urban, semi‐urban and rural locations. Focus group conversations were recorded, transcribed and analysed thematically. Results: The themes that emerged were around low expectations for both general health and oral health. A communal responsibility for health was expressed, and both money and transport were identified as key barriers to accessing care. Participants recognised that they had oral health problems, and acknowledged the impact of poor oral function on health and nutrition. Conclusion: This study is an important first step in better understanding the oral health experiences and perceptions of older people in Cambodia. Participants described the impacts of poor oral health as being important, even when compared with other general health conditions.